Intra-Arterial Thrombolysis for Acute Central Retinal Artery Occlusion: A Systematic Review and Meta-Analysis - Page, Paul S.; Khattar, Nicolas K.; White, Andrew C.; Cambon, Alexander C.; Brock, Guy N.; Rai, Shesh N.; James, Robert F. (Frontiers in Neurology, 2018)
Background and Purpose: Acute central retinal artery occlusion (CRAO) is a serious ophthalmologic emergency that may result in monocular blindness. To date, studies evaluating intra-arterial thrombolysis (IAT) have not shown a definitive clinical benefit. We have conducted a systematic review with a meta-analysis to effectively evaluate this treatment option. Methods: A systematic literature search was focused on studies containing five or more patients undergoing intra-arterial thrombolysis that included a control group treated with standard therapy. Pooled meta-analysis was performed. Results: Five retrospective controlled studies and one randomized clinical trial were identified satisfying all inclusion criteria resulting in the analysis of 236 patients treated with intra-arterial thrombolysis and 255 patients treated with standard therapy. A pooled fixed effects analysis resulted in an estimated odds ratio of 2.52, 95% CI [1.69, 3.77], (P<0.0001) favoring intra-arterial thrombolysis. Conclusion: IAT is a promising therapeutic option for CRAO with great potential. Further randomized trials are needed to establish a significant benefit and ensure the safety of the intervention.